Three-dimensional imaging of vortex structure in a ferroelectric nanoparticle driven by an electric field; Nature Communications; Vol. 8, iss. 1 - Karpov D. A. Dmitriy Andreevich; Liu Z.; Rolo T. Tomy Dos Santos; Harder R. S. Ross; Balachandran P. V. Prasanna; Xue D. Di; Lookman T. Turab; Fohtung E. (2017, 2017)
Title screen